Малогабаритный цифровой частотомер с высокой разрешающей способностью - Krival, I. I.; Skrypnyuk, A. I.; Protsenko, V. A.; Maryenko, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
Principle of operation, brief technical and metrological characteristics of frequency counter UA Ч3-64/2 are observed. In addition to the frequency signal parameters, the frequency counter can also measure the time intervals with high resolution, and it also has the channel of general usage and RS-232 interfaces. It can be classified as high-precision measuring device that can operate in standalone mode as well as a part of complex metrology systems. Frequency counter belongs to the category of exemplary measurement devices.